Dynamics of ovarian maturation during the reproductive cycle of Metynnis maculatus, a reservoir invasive fish species (Teleostei: Characiformes) - Pereira, Thiago Scremin Boscolo; Moreira, Renata Guimaraes; Batlouni, Sergio Ricardo (Sociedade Brasileira de Ictiologia, 2013)
Neste estudo, avaliamos a dinâmica da maturação ovariana a desova durante o ciclo reprodutivo de Metynnis maculatus. Fêmeas adultas (n = 36) foram coletadas bimestralmente entre abril de 2010 e março de 2011. O índice gonadossomático (IGS) foi calculado e amostras de ovário e de sangue foram submetidas à avaliação morfométrica e das concentrações plasmáticas dos esteroides por ELISA, respectivamente. A espécie apresenta desenvolvimento ovariano assincrônico, com múltiplas desovas. Neste estudo revelamos que mesmo sendo de desova parcelada, os ovários do M. maculatus mostraram um padrão de desenvolvimento com predomínio de atividade vitelogênica entre abril a agosto e intensificação da desova em setembro. Em outubro houve uma diminuição nos valores médios de IGS, bem como registramos as maiores frequências de folículos pós-ovulatórios (FPOs). Observamos uma correlação positiva entre a frequência de FPOs e a concentração plasmática de 17 α-OHP. O M. maculatus tem potencial para ser usado como fonte para uso de hipófise para preparo de extrato bruto para indução hormonal, sendo o período teórico para coleta de hipófises de setembro a outubro, mas estudos específicos para esta finalidade ainda precisam ser desenvolvidos.

In this study, we evaluated the dynamics of ovarian maturation and the spawning processes during the reproductive cycle of Metynnis maculatus. Adult females (n = 36) were collected bimonthly between April 2010 and March 2011. The mean gonadosomatic index (GSI) was determined, ovarian and blood samples were submitted for morphometric evaluation and the steroid plasma concentration was determined by ELISA. This species demonstrated asynchronous ovarian development with multiple spawns. This study revealed that, although defined as a multiple spawning species, the ovaries of M. maculatus have a pattern of development with a predominance of vitellogenesis between April and August and have an intensification in spawning in September; in October, a drop in the mean GSI values occurred, and the highest frequencies of post-ovulatory follicles (POFs) were observed. We observed a positive correlation between the POF and the levels of 17α-hydroxyprogesterone. Metynnis maculatus has the potential to be used as a source of pituitary tissue for the preparation of crude extracts for hormonal induction; the theoretical period for use is from September to December, but specific studies to determine the feasibility of this approach must be conducted.
Keywords: Multiple spawns; Oocyte development; Spawning season; Steroid levels